Correlation of facilities of training work of weightlifters of high qualification of different weight categories - Shymechko I. M. (Kharkov National Pedagogical University, 2011)
The individual model parameters of volume and intensity of training work of sportsmen are analysed on the groups of exercises. In researches 5 sportsmen of collapsible command of Ukraine took part on heavy athletics. The necessity of conduct and analysis of documents of planning and account of training work is marked. The variants of partition of training load are resulted in the areas of intensity depending on the period of preparation (4 microcycle). The tendencies of change of correlation of facilities of training depending on the weight category of sportsmen are set. The quantitative indexes of volume and intensity of the training loading are recommended on the groups of exercises.